1991
DOI: 10.1093/ajcp/95.4.517
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotyping of Non-Hodgkin's Lymphoma in Paraffin-Embedded Tissue Sections: A Comparison with Genotypic Analysis

Abstract: Several monoclonal antibodies (MoAbs) are now available for immunophenotyping non-Hodgkin's lymphomas (NHLs) in paraffin-embedded tissue sections. To determine the reliability of these reagents in predicting the genotype, 44 cases of NHL were studied with the alkaline phosphatase-anti-alkaline phosphatase technique with the use of the following MoAbs: leukocyte common antigen (CD45), Mac 387, L26, 4KB5, MB1, MB2, LN2, UCHL1, MT1, and MT2. The lineage of the neoplastic cells was determined in all cases by gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…25,26 Similarly, most investigators have failed to detect L26 reactivity with T-cell neoplasms. 1415,24,27,28 However, some investigators have reported rare L26-positive T-cell lymphomas, 16,22,23,25,26 ' 29 which are thought to be derived from a small population of normal lymphocytes that co-express CD3 and small amounts of CD20. 26 These L26-positive T-cell neoplasms, which were classified morphologically as DM (5) or DL (3) lymphomas, 16,22,23,26,29 exhibited, where described, distinct membrane staining, characteristic of L26 reactivity with B-cell NHLs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Similarly, most investigators have failed to detect L26 reactivity with T-cell neoplasms. 1415,24,27,28 However, some investigators have reported rare L26-positive T-cell lymphomas, 16,22,23,25,26 ' 29 which are thought to be derived from a small population of normal lymphocytes that co-express CD3 and small amounts of CD20. 26 These L26-positive T-cell neoplasms, which were classified morphologically as DM (5) or DL (3) lymphomas, 16,22,23,26,29 exhibited, where described, distinct membrane staining, characteristic of L26 reactivity with B-cell NHLs.…”
mentioning
confidence: 99%
“…1415,24,27,28 However, some investigators have reported rare L26-positive T-cell lymphomas, 16,22,23,25,26 ' 29 which are thought to be derived from a small population of normal lymphocytes that co-express CD3 and small amounts of CD20. 26 These L26-positive T-cell neoplasms, which were classified morphologically as DM (5) or DL (3) lymphomas, 16,22,23,26,29 exhibited, where described, distinct membrane staining, characteristic of L26 reactivity with B-cell NHLs. However, at least two of these T-cell neoplasms also reacted with one or more other preferential B-cell antibodies, 16 ' 22 suggesting that these L26-positive T-cell NHLs exhibit other phenotypic characteristics of B cells than just CD20 expression.…”
mentioning
confidence: 99%
“…-directed against the T-cell-associated CD45RO antigen (both DAKO) (12). Visualization was performed us,ng a streptavidin-biotin technique.…”
Section: Methodsmentioning
confidence: 99%
“…Southern blotting is limited for diagnostic work because it is time-consuming and complex, and requires the use of radioactive isotopes and large amounts of DNA. In addition, it is not well suited to the study of formalin-fixed and paraffin-embedded material because of the consequent DNA degeneration [6][7][8][9]. Although immunohistologic studies for the detection of immunoglobulin light chains have been widely employed to determine monotypic restriction, the results have not been consistently successful, particularly with formalin-fixed and paraffin-embedded sections [10,11].…”
Section: Introductionmentioning
confidence: 99%